PENGOLAHAN ARSIP FOTO PEMUGARAN CANDI BOROBUBUR DI BALAI KONSERVASI BOROBUDUR - , NUR DIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This result describes about how to arrange photograph archives of Borobudur Templeâs restoration in Borobudur Conservation Office. The photograph archives contains of evidental â historical information which must be processed properly. This arrangement of photograph archives done by doing direct practice in Borobudur Conservation Office. The objective of this finding is making the photograph archives of maintained well. The research is using three collecting data. They are: literature review, observation participation and interview. Here is the breakdown of the methods. Literatur review which is done by collecting data from the books source. Meanwhile, observation participation which is done by conducting a direct review and photograph archives arrangement practices to determine the real situation. The last is interview, which is done by asking a question to Mr. Rifqi Kurniadi Suryanto, A. Md as the staff of Documentary and Publishing department in Borobudur Conservation Office. The conclusion of this research is arranging the photograph archives is necessary to be done by the the researcher to maintain or save the authentic archive and information on it. The steps of this research is starting from taking photograph archives from the Roll OâPack 1 bookselves, describing it, entering it the computer, doing digitalization on it, saving it and the last is finding the aids of it. The arrangement of restoration photograph archives in Borobudur Conservation Office is still having obstacles, which are from human resourches, information access, means and the material of arranging it.